OPTIMAL POWER FLOW DENGAN OPTIMAL PLACEMENT TCSC DEVICE MENGGUNAKAN METODE GENETIC ALGORITHM - , CHICO HERMANU B. A.; , Dr. Ir. Sasongko Pramono Hadi, DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
With ever-increasing demand for electricity and complexity of power system, optimal operation power system issue becomes important. Optimal power flow (OPF) with optimal placement and rating of thyristor controlled series capacitor (TCSC) have been proposed as an effective solution for determining economic dispatch and controlling power flow in electrical power systems. TCSC is one of type flexible alternating current transmission systems (FACTS) as an effective for controlling transmission line impedance. TCSC is able to decrease the total cost of generation, to enhance the steady state stability, to increase the transfer power capabiliity, to improve the voltage profile, and to reduce the transmission line losses. The purpose this study to minimize total cost of generation with the optimal placement and rating of TCSC which use genetic algorithm-design of experiment techniques (GA-DOE) method. To validate the proposed method, simulations are implemented on an IEEE 30-bus power system and Java-Bali 500 kV power system. The results for IEEE-30 bus system, total cost of generation is 0,03% more cheaper than OPF without TCSC. The optimal location of one TCSC compensator in line (2-5) with level compensation -0,2550 Xline. The simulation results for Java-Bali 500 kV with 5 TCSC compensator, the proposed method can reduced total cost of generation is 0,12% compared with OPF without TCSC.